Pengaruh Struktur Modal, Ukuran Perusahaan, dan Nilai Perusahaan terhadap Profitabilitas Pada Sektor Perbankan yang Terdaftar di Bursa Efek Indonesia Periode 2020-2024 - Hajar Chair Arrachman; Sri Yulandasari Lajai Mandam; Alfiana Alfiana (Indo Publishing, 2026)
This study aims to analyze the influence of capital structure, firm size, and firm value on profitability in the banking sector listed on the Indonesia Stock Exchange for the 2020–2024 period. This study uses a quantitative approach with secondary data in the form of annual financial reports of banking companies. The results show that capital structure has a positive and significant effect on profitability, while firm size has no significant effect on profitability. Firm value has a positive and significant effect on profitability. However, simultaneously, capital structure, firm size, and firm value have no significant effect on profitability. These findings indicate that banking profitability is influenced not only by internal company factors but also by other factors.